2007
DOI: 10.1021/jf062809m
|View full text |Cite
|
Sign up to set email alerts
|

Active Package for Wild Strawberry Fruit (Fragaria vescaL.)

Abstract: An antimicrobial active package has been developed to improve the safety and quality of wild strawberries, as well as extending their shelf life. The fruits were packed in equilibrium-modified atmosphere packaging (EMAP), and the effect on Botrytis cinerea growth and on the quality parameters of the fruit by the addition of different amounts of 2-nonanone, an antifungal volatile compound naturally present in strawberries, was investigated during storage at 10 and 22 degrees C. The temperature of 10 degrees C w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Titratable acidity was the predominant organic acid in strawberry and its decrease was related to maturation. This decrease was also found when strawberry was stored with high oxygen atmosphere during 14‐d storage (Zheng and others 2007), and an active packing material (Almenar and others 2007). Ascorbic acid is one of the most abundant antioxidant present in strawberry fruit.…”
Section: Resultsmentioning
confidence: 77%
“…Titratable acidity was the predominant organic acid in strawberry and its decrease was related to maturation. This decrease was also found when strawberry was stored with high oxygen atmosphere during 14‐d storage (Zheng and others 2007), and an active packing material (Almenar and others 2007). Ascorbic acid is one of the most abundant antioxidant present in strawberry fruit.…”
Section: Resultsmentioning
confidence: 77%
“…subtilis JA were identified by GC/MS analysis. The antifungal nature of some of the compounds, such as 2-ethyl-hexanol, 2,4-bis(2-methylpropyl)-phenol, 4-hydroxybenzaldehyde and 2-nonanone, have already been demonstrated in several pathogen systems (Fernando et al 2005, Gershon et al 1995, Wang et al 2005, Almenar et al 2007). Our results demonstrated that Bac.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was hypothesized that internal moisture can be the driving force that released the antimicrobial compound from the complex. Reports showed that the inclusion complexes b-cyclodextrin-hexanal (1.1 lL hexanal/L) and b-cyclodextrin-acetaldehyde (0.12 lL acetaldehyde/L) were effective against Alternaria alternata, Colletotrichum acutatum and Botrytis cinerea (Almenar et al 2007). A sachet containing different concentrations of 2-nonanone (2.5, 5 and 10 lL), volatile compounds that are naturally found in strawberry fruit, impregnated in alumina as adsorbent solid was developed, studied and finally incorporated as a part of the active packaging system.…”
Section: Active Packagingmentioning
confidence: 99%
“…A sachet containing different concentrations of 2-nonanone (2.5, 5 and 10 lL), volatile compounds that are naturally found in strawberry fruit, impregnated in alumina as adsorbent solid was developed, studied and finally incorporated as a part of the active packaging system. The final package increased the shelf-life of wild strawberries, delayed fungal decay and maintained the overall quality of the fruits (Almenar et al 2007). It has to be remarked that among the different kinds of active packages, headspace artifacts have been successfully used to preserve fresh products, even industrially.…”
Section: Active Packagingmentioning
confidence: 99%